Defective carbon material loaded molybdenum disulfide-based composite material X-CTAB-Y as well as preparation and application thereof
By using defective carbon materials to support molybdenum disulfide-based composites in electrocatalysts, the problems of existing electrocatalysts being easily corroded in acidic media and limited precious metal resources are solved, and efficient and stable electrocatalytic hydrogen evolution is achieved, reducing the cost of hydrogen energy preparation.
Patent Information
- Application Number
- CN202411905233.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing electrocatalysts are prone to corrosion in acidic media, have short lifespan, and have limited precious metal resources, which leads to high cost of electrolyzing hydrogen production, making it difficult to achieve large-scale application.
The defective carbon material is loaded with molybdenum disulfide-based composite X-CTAB-Y, and is prepared by stirring and hydrothermal method. The nickel single atoms are loaded with oxidation to form heterojunctions, improving the corrosion resistance and cycling performance of the electrocatalyst.
Electrocatalytic hydrogen evolution with low overpotential and high cyclic performance in acidic media is achieved, reducing the cost of electrocatalysts and improving the efficiency and sustainability of hydrogen energy preparation.
Smart Images

Figure CN119725577A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen energy technology, and in particular to a defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y and the preparation and application thereof. Background Art
[0002] With economic development, energy demand continues to grow, and the environmental problems caused by human use of fossil energy are becoming increasingly serious. However, with the excessive exploitation and use of fossil energy, a series of difficulties and challenges have followed, including limited crustal reserves, the depletion of surface fossil energy, which has led to restrictions on mining deep in the crust and cost constraints. More importantly, the environmental problems caused by the large-scale use of fossil energy have had a very negative impact on human daily production and life. Harmful gases produced during the use of fossil energy, such as CO2, NO x and SO x , in the long run, will cause irreversible damage to the environment. Promoting the development of sustainable energy has become an inevitable trend today. my country is committed to energy conservation, emission reduction and energy structure transformation, but it needs to solve the problem of storage and sustainable use of renewable energy. Hydrogen energy is an ideal high energy density (142.35kJ kg -1 ) is a secondary energy source. The only combustion product is water. Unlike fossil energy, it does not produce by-products. It is one of the best clean energy sources. In addition to its high energy density, hydrogen energy has the following advantages: the raw materials for the preparation of hydrogen energy are abundant, and hydrogen energy can be directly produced from water; hydrogen energy storage and transportation are very convenient. It can be stored in high-pressure tanks in gaseous or liquid form, or stored in solid hydrogen storage materials. Therefore, hydrogen energy has immeasurable application prospects in solving the environmental pollution problems and energy shortage crisis caused by fossil energy. At present, the preparation of hydrogen energy is still in its infancy. Hydrogen is mainly prepared by chemical methods such as water gas reforming, which will be accompanied by the generation of pollutants and is difficult to meet the requirements of clean preparation. As a method for preparing high-purity hydrogen, water electrolysis for hydrogen production does not produce greenhouse gases during the preparation process, and the purity of the produced hydrogen can reach more than 99.7%, which is enough to meet the requirements of actual production. However, water electrolysis for hydrogen production cannot be applied on a large scale today. Compared with the theoretical water decomposition voltage of 1.23V, it has a large overpotential, resulting in high cost and poor promotion.
[0003] In the production of hydrogen by electrolysis of water, an efficient electrocatalyst is required. This electrocatalyst should have a low overpotential to achieve an efficient electrochemical reaction. At present, the electrocatalysts mainly include: precious metal-based electrocatalysts, transition metal-based electrocatalysts, and non-metal-based electrocatalysts. Among them, platinum-based catalysts have been commercialized due to their high efficiency and stable performance, but due to their extremely rare content in the earth's crust, the cost of electrocatalysts has become high, so it is necessary to replace the structure of non-precious metal catalysts. The development of efficient, stable and scalable low-cost electrocatalysts is the key to realizing the "hydrogen economy" blueprint. Reasonable design of transition metal-based electrocatalysts can solve the key problems of the high price of current electrocatalysts and limited precious metal resources. However, in acidic media, transition metal-based electrocatalysts have the disadvantages of being easily corroded and having a short lifespan, so it is necessary to construct acid-resistant carbon carrier composite materials to increase the corrosion resistance and long lifespan of their electrocatalysts. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a defective carbon material loaded molybdenum disulfide based composite material X-CTAB-Y and its preparation and application.
[0005] The first object of the present invention is to provide a defective carbon material loaded molybdenum disulfide-based composite material X-CTAB-Y, with the defective carbon material as a carrier, and the molybdenum disulfide-based composite material is loaded on the surface and defects of the carrier, wherein X is the defective carbon material and Y is the molybdenum disulfide-based composite material.
[0006] In the present invention, the defective carbon material loaded molybdenum disulfide based composite material X-CTAB-Y includes defective carbon material loaded molybdenum disulfide X-CTAB-MoS2, the molybdenum disulfide based composite material Ni SA / X-CTAB-MoS2 loaded with nickel single atoms, the carbon material loaded molybdenum disulfide based composite material X-CTAB-MoS2-MoO3, the carbon material loaded molybdenum disulfide based composite material Ni SA / X-CTAB-MoS2-MoO3, and the carbon material loaded molybdenum disulfide based composite material X-CTAB-MoS2-SD.
[0007] In some embodiments of the present invention, the defective carbon material includes one or more of reduced graphene oxide, carbonitride C3N4, and carbon nanotubes.
[0008] In some embodiments of the present invention, the molybdenum disulfide-based composite material includes one or more of a molybdenum disulfide and nickel single atom complex, a molybdenum disulfide and molybdenum trioxide heterojunction, and a molybdenum disulfide and sulfur-deficient molybdenum disulfide heterojunction.
[0009] The second object of the present invention is to provide a method for preparing the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y, comprising the following steps:
[0010] Defective carbon material, CTAB and sulfur source are stirred to obtain X-CTAB-S;
[0011] The obtained X-CTAB-MoS2 is then reacted with a molybdenum source by a hydrothermal method, and single-atom nickel is loaded on the obtained X-CTAB-MoS2 and / or oxidized to form a heterojunction, and / or sulfur vacancies are formed in situ by high-temperature heat treatment to prepare the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y.
[0012] In some embodiments of the present invention, the mass ratio of the defective carbon material, CTAB, and sulfur source is (20:1:80)-(40:1:60);
[0013] The defective carbon material includes one or more of reduced graphene oxide, carbonitride C3N4, and carbon nanotubes;
[0014] The conditions of the hydrothermal method are: 150-300°C and 24-48h;
[0015] The molybdenum source is selected from one or more of Na2MoO4·2H2O, K2MoO4, CaMoO4, FeMoO4, (NH4)2MoO4, and MgMoO4;
[0016] The sulfur source is selected from one or more of sublimated sulfur, sodium sulfide and cysteine.
[0017] In some embodiments of the present invention, the steps of preparing Ni SA / X-CTAB-MoS2 by loading single-atom nickel are as follows:
[0018] Defective carbon material, CTAB and sulfur source are stirred to obtain X-CTAB-S;
[0019] Then, the defective carbon material-loaded molybdenum disulfide composite material X-CTAB-MoS2 is prepared by reacting with a molybdenum source through a hydrothermal method;
[0020] The defective carbon material-loaded molybdenum disulfide composite material is mixed with a nickel source, and stirred to react under ultraviolet light to obtain the molybdenum disulfide-based composite material Ni SA / X-CTAB-MoS2 loaded with nickel single atoms.
[0021] In some embodiments of the present invention, the mass ratio of the X-CTAB-MoS2 to the nickel source is (1:0.05)-(1:0.2);
[0022] The conditions of the hydrothermal method are: 150-300°C and 24-48h;
[0023] The nickel source is selected from one or more of Ni(NO3)2, nickel chloride, and nickel sulfate;
[0024] The sulfur source is selected from one or more of sublimated sulfur, sodium sulfide, and cysteine;
[0025] The stirring reaction time is 4-8h.
[0026] In some embodiments of the present invention, the steps of oxidizing X-CTAB-MoS2 to form a heterojunction X-CTAB-MoS2-MoO3 are:
[0027] Defective carbon material, CTAB and sulfur source are stirred to obtain X-CTAB-S;
[0028] Then, the carbon material-loaded molybdenum disulfide-based composite material X-CTAB-MoS2 is prepared by reacting with a molybdenum source through a hydrothermal method;
[0029] The X-CTAB-MoS2 and the oxidant are stirred and mixed to react, and dried to obtain the X-CTAB-MoS2-MoO3;
[0030] In the present invention, the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-MoS2-MoO3 is oxidized on the surface of the carbon material-loaded molybdenum disulfide composite material to form MoO3, wherein X is a defective carbon material.
[0031] The stirring and mixing reaction time is 12-24h.
[0032] In some embodiments of the present invention, the oxidant is selected from one or more of H2O2, KMnO4, NaClO3 and NaClO4;
[0033] The molybdenum source is selected from one or more of Na2MoO4·2H2O, K2MoO4, CaMoO4, FeMoO4, (NH4)2MoO4, and MgMoO4;
[0034] The sulfur source is selected from one or more of sublimated sulfur, sodium sulfide and cysteine.
[0035] In some embodiments of the present invention, the steps of loading single-atom nickel on X-CTAB-MoS2 and oxidizing to form a heterojunction Ni SA / X-CTAB-MoS2-MoO3 are as follows: X-CTAB-MoS2 is stirred and mixed with an oxidant to react, and dried to obtain X-CTAB-MoS2-MoO3, and the X-CTAB-MoS2-MoO3 is mixed with a nickel source, and stirred and reacted under ultraviolet light to obtain the Ni SA / X-CTAB-MoS2-MoO3;
[0036] In the present invention, Ni SA / X-CTAB-MoS2-MoO3 uses X-CTAB-MoS2-MoO3 as a carrier, and nickel single atoms are loaded on the surface of the carrier.
[0037] In some embodiments of the present invention, the step of forming X-CTAB-MoS2-SD by in-situ forming sulfur vacancies in X-CTAB-MoS2 through high-temperature heat treatment is as follows: the X-CTAB-MoS2 is mixed and ground with a molten salt mixture, and high-temperature calcined under an inert gas atmosphere to obtain the X-CTAB-MoS2-SD.
[0038] In the present invention, a defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-MoS2-SD is provided, wherein sulfur vacancies are formed in situ by heating the surface of the X-CTAB-MoS2 at high temperature. SD in the X-CTAB-MoS2-SD is sulfur-defective molybdenum sulfide MoS z ; The sulfur-deficient molybdenum sulfide MoS z of 1 <Z<2。
[0039] In some embodiments of the present invention, the mass ratio of the X-CTAB-MoS2 to the molten salt mixture is (1:2)-(2:1);
[0040] The temperature of high temperature calcination is 400-800°C, and the time of high temperature calcination is 2-6h;
[0041] The inert gas of the inert atmosphere includes argon and / or nitrogen;
[0042] The molten salt mixture is selected from two or more of KCl, LiCl and NaCl.
[0043] The third object of the present invention is to provide an application of the defective carbon material-supported molybdenum disulfide-based composite material X-CTAB-Y in electrocatalytic hydrogen evolution under acidic conditions.
[0044] In some embodiments of the invention, the acidic pH range is 0-5.
[0045] The fourth object of the present invention is to provide an application of the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y in a hydrogen production electrolyzer and a fuel cell.
[0046] The above technical solution of the present invention has the following advantages compared with the prior art:
[0047] 1. The basic raw materials are cheap and easy to obtain, the process is simple and efficient, and it is easy to scale up the preparation.
[0048] 2. The defective carbon material (such as reduced graphene oxide) loaded molybdenum disulfide-based composite material of the present invention has more active sites. The defective carbon material (such as reduced graphene oxide) loaded molybdenum disulfide-based composite material of the present invention has low overpotential, good cycle performance and corrosion resistance in acidic medium.
[0049] 3. The composite material obtained in the present invention exhibits excellent electrocatalytic performance due to the synergistic effect of its defective carbon material (such as reduced graphene oxide rGO) and Ni single atom, molybdenum disulfide, molybdenum trioxide, and sulfur-defective molybdenum sulfide, and the 1T phase MoS2 therein better anchors the Ni single atom on the composite material and provides a larger specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0051] Figure 1 TEM image of the Ni SA / rGO-CTAB-MoS2 composite material prepared in Example 1 of the present invention;
[0052] Figure 2 This is a spherical aberration diagram of the Ni SA / rGO-CTAB-MoS2 composite material prepared in Example 1 of the present invention;
[0053] Figure 3 The three-dimensional reconstruction and mapping diagram of the Ni SA / rGO-CTAB-MoS2 composite material prepared in Example 1 of the present invention;
[0054] Figure 4 HER performance diagram of the Ni SA / rGO-CTAB-MoS2 composite material prepared in Example 1 of the present invention in an acidic medium;
[0055] Figure 5 This is the XRD pattern of the rGO-CTAB-MoS2-MoO3 composite material prepared in Example 5 of the present invention;
[0056] Figure 6 This is a SEM image of the rGO-CTAB-MoS2-MoO3 composite material prepared in Example 5 of the present invention;
[0057] Figure 7 HER performance diagram of the Ni SA / rGO-CTAB-MoS2-MoO3 composite material prepared in Example 5 of the present invention in an acidic medium;
[0058] Figure 8 This is a SEM image of the SD-rGO-CTAB-MoS2-MoO3 composite material prepared in Example 7 of the present invention;
[0059] Fig. 9 This is the XRD pattern of the SD-rGO-CTAB-MoS2-MoO3 composite material prepared in Example 7 of the present invention.
[0060] Fig.10 This is a diagram of the HER performance of the SD-rGO-CTAB-MoS2-MoO3 composite material prepared in Example 7 of the present invention in an acidic medium.
[0061] Fig.11 XRD diagrams of rGO-CTAB-MoS2 and Ni SA / rGO-CTAB-MoS2 composite materials prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0062] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0063] Example 1
[0064] This embodiment provides a method for preparing a reduced graphene oxide-supported molybdenum disulfide-based composite electrocatalyst Ni SA / rGO-CTAB-MoS2, as follows:
[0065] 1. Preparation of rGO-CTAB-MoS2:
[0066] Step (i), take 70 mL of 1 mg / mL graphene oxide suspension GO and 66 mg of CTAB powder and stir for 2 h, and set aside;
[0067] Step (ii), 787.5 mg of Na2S·9H2O and 315 mg of sublimed sulfur were stirred for 2 h and set aside;
[0068] Step (iii), mix the mixture of step (i) and step (ii), stir overnight. Then, add HCOOH dropwise to the mixture, stir for 2 hours, and filter with acetone and water to obtain rGO-CTAB-S for standby use;
[0069] Step (iv), take 100 mg of the rGO-CTAB-S powder obtained in step (iii), add 302 mg of the molybdenum source Na2MoO4·2H2O and 70 mL of deionized water, and carry out hydrothermal reaction at 200°C and 24 h. The obtained solution is filtered and dried to obtain rGO-CTAB-MoS2, and the obtained material is structurally characterized. Fig.11 .
[0070] 2. Preparation of Ni SA / rGO-CTAB-MoS2: The rGO-CTAB-MoS2 obtained above was dispersed in deionized water to form a mixed solution, mixed with Ni(NO3)2·6H2O in a mass ratio of 1:0.05, and stirred for 4 hours; then stirred for 4 hours under ultraviolet light, filtered with ethanol and deionized water, and dried overnight in an oven at 60°C to obtain Ni SA / rGO-CTAB-MoS2.
[0071] Structural characterization:
[0072] The rGO-CTAB-MoS2 and Ni SA / rGO-CTAB-MoS2 prepared above were structurally characterized. The experimental results are shown in Figures 1 to 3 and Fig.11 , by XRD( Fig.11 )、TEM( Figure 1 )、Spherical aberration diagram( Figure 2 ), 3D reconstruction and mapping ( Figure 3 ) can prove that Ni single atoms were successfully loaded onto rGO-CTAB-MoS2, indicating that Ni SA / rGO-CTAB-MoS2 was successfully prepared.
[0073] Performance Test:
[0074] The electrocatalytic performance of the prepared Ni SA / rGO-CTAB-MoS2, rGO-CTAB-MoS2 and the control group pristineMoS2 and 20wt% Pt / C was tested in a 0.5M H2SO4 medium, as follows:
[0075] Step 1: Take 5 mg of rGO-CTAB-MoS2, Ni SA / rGO-CTAB-MoS2 and the control group pristineMoS2, 20 wt% Pt / C and 2 mL of isopropanol, 460 μL of deionized water and 20 μL of Nafion, and mix them evenly by ultrasound to form a 2 mg / mL ink solution for standby use.
[0076] Step 2: Apply the ink droplets onto the glassy carbon electrode and characterize the electrochemical performance in an acidic medium of 0.5M H2SO4. The experimental results are shown in Figure 4 ,Depend on Figure 4 It can be seen that Ni SA / rGO-CTAB-MoS2 exhibits lower overpotential and stronger hydrogen evolution performance than rGO-CTAB-MoS2 and MoS2.
[0077] Example 2
[0078] Same as Example 1, except that, in step 1, the conditions of the hydrothermal method are: 200° C. and 30 h.
[0079] Example 3
[0080] The same as Example 1, the difference is that in step 1, the graphene oxide suspension GO is replaced by carbonitride C3N4.
[0081] Example 4
[0082] The same as Example 1, the difference is that in step 2, the mass ratio of the rGO-CTAB-MoS2 to the nickel source is (1:0.2).
[0083] Example 5
[0084] The same as Example 1, except that in step 1, the molybdenum source is replaced by K2MoO4.
[0085] Example 6
[0086] This embodiment provides a method for preparing a reduced graphene oxide-supported molybdenum disulfide-based electrocatalyst Ni SA / rGO-CTAB-MoS2-MoO3, which is as follows:
[0087] 1. The rGO-CTAB-MoS2 obtained in Example 1 was dispersed in deionized water to form a solution, and stirred with 2.5wt% H2O2 for 12h. The obtained mixed solution was filtered with ethanol and deionized water, placed in a vacuum drying oven, and dried overnight at 60°C to obtain rGO-CTAB-MoS2-MoO3.
[0088] Structural characterization:
[0089] The obtained rGO-CTAB-MoS2-MoO3 was characterized by XRD and SEM. Figure 5 and Figure 6 ,Depend on Figure 5 It can be seen that the heterojunction composite rGO-CTAB-MoS2-MoO3 has the coexistence of MoO3 and MoS2. Figure 6 It can be seen that the composite material rGO-CTAB-MoS2-MoO3 was successfully constructed.
[0090] 2. Mix the obtained rGO-CTAB-MoS2-MoO3 and Ni(NO3)2·6H2O in a mass ratio of 1:0.05 and stir for 4 hours; then stir for 4 hours under ultraviolet light, filter with ethanol and deionized water, and dry overnight in an oven at 60°C to obtain Ni SA / rGO-CTAB-MoS2-MoO3.
[0091] Structural characterization:
[0092] The obtained Ni SA / rGO-CTAB-MoS2-MoO3 was structurally characterized by XRD ( Figure 5 ), SEM and mapping( Figure 6 ) is characterized. Figure 5 , 6 It can be seen that the material was successfully prepared.
[0093] Performance Test:
[0094] The obtained Ni SA / rGO-CTAB-MoS2-MoO3, rGO-CTAB-MoS2-MoO3 and the control groups rGO, pristine MoS2, 20wt% Pt / C, and rGO-CTAB-MoS2 were tested for electrocatalytic performance in a medium of 0.5M H2SO4, as follows:
[0095] Step 1: Take 5 mg of Ni SA / rGO-CTAB-MoS2-MoO3, rGO-CTAB-MoS2-MoO3 and the control group pristine MoS2, 20 wt% Pt / C, 2 mL of isopropanol, 460 μL of deionized water and 20 μL of Nafion, and mix them into 2 mg / mL ink solution by ultrasonication for standby use.
[0096] Step 2: Apply the ink droplets onto the glassy carbon electrode and characterize the electrochemical performance in an acidic medium of 0.5M H2SO4. Figure 7 The successfully constructed heterojunction rGO-CTAB-MoS2-MoO3 has better performance than pristine MoS2 and rGO-CTAB-MoS2. Single-atom Ni is loaded on the heterojunction to form a composite material rGO-CTAB-MoS2-MoO3 with even better performance, and can be stably circulated in acidic media, with efficient long-term hydrogen evolution.
[0097] Example 7
[0098] The same as Example 6, except that the nickel source in step 2 is replaced with nickel sulfate.
[0099] Example 8
[0100] The embodiment of the present invention provides a method for preparing rGO-CTAB-MoS2-SD, which is specifically as follows:
[0101] 1.50 g of rGO-CTAB-MoS2 obtained in Example 1 was ground with 1.35 g of KCl and 1.15 g of LiCl by the molten salt method. After sufficient grinding, it was placed in a tube furnace and calcined at 500°C for 4 h in an Ar atmosphere. After filtration with deionized water, it was dried in a drying oven at 60°C overnight to obtain rGO-CTAB-MoS2-SD with sulfur vacancies, where SD is sulfur-deficient molybdenum sulfide MoSz (1 <Z<2)。
[0102] Structural characterization:
[0103] The structure of the obtained rGO-CTAB-MoS2-SD was characterized by SEM and mapping ( Figure 8 )、XRD( Fig. 9 ) is characterized. Figure 8 , 9 It can be seen that the material successfully prepared sulfur vacancies.
[0104] Performance Test:
[0105] The obtained rGO-CTAB-MoS2-SD, rGO-CTAB-MoS2 and the control group MoS2, Pt / C were tested for electrocatalytic performance in a 0.5M H2SO4 medium, as follows:
[0106] Step 1: Take 5 mg of rGO-CTAB-MoS2-SD, rGO-CTAB-MoS2, and the control group MoS2, Pt / C, 2 mL of isopropanol, 460 μL of deionized water, and 20 μL of Nafion, and mix them evenly by ultrasound to form a 2 mg / mL ink solution for standby use.
[0107] Step 2: Apply the ink droplets onto the glassy carbon electrode and characterize the electrochemical performance in an acidic medium of 0.5M H2SO4. Fig.10 The composite material SD-rGO-CTAB-MoS2 with sulfur vacancies has a lower overpotential, a smaller Tafel slope, a larger electrochemical surface area in acidic media, and can produce hydrogen stably and efficiently.
[0108] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A defective carbon material loaded molybdenum disulfide based composite material X-CTAB-Y, characterized in that: The defective carbon material is used as a carrier, and the molybdenum disulfide-based composite material is loaded on the surface and defects of the carrier, wherein X is the defective carbon material and Y is the molybdenum disulfide-based composite material.
2. The defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y according to claim 1, characterized in that: The defective carbon material includes one or more of reduced graphene oxide, carbonitride C3N4, and carbon nanotubes; The molybdenum disulfide-based composite material includes one or more of a molybdenum disulfide and nickel single atom composite, a molybdenum disulfide and molybdenum trioxide heterojunction, and a molybdenum disulfide and sulfur-deficient molybdenum disulfide heterojunction.
3. A method for preparing the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y as claimed in claim 1 or 2, characterized in that: The following steps are involved: Defective carbon material, CTAB and a sulfur source are subjected to a stirring method to obtain X-CTAB-S; then, the defective carbon material is reacted with a molybdenum source through a hydrothermal method to obtain X-CTAB-MoS2; the obtained X-CTAB-MoS2 is loaded with single atomic nickel and / or oxidized to form a heterojunction, and / or sulfur vacancies are formed in situ through high-temperature heat treatment to obtain the defective carbon material loaded molybdenum disulfide-based composite material X-CTAB-Y.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the defective carbon material, CTAB and sulfur source is (20:1:80)-(40:1:60); The defective carbon material includes one or more of reduced graphene oxide, C3N4, and carbon nanotubes; The conditions of the hydrothermal method are: 150-300°C and 24-48h; The molybdenum source is selected from one or more of Na2MoO4·2H2O, K2MoO4, CaMoO4, FeMoO4, (NH4)2MoO4, and MgMoO4; The sulfur source is selected from one or more of sublimated sulfur, sodium sulfide and cysteine.
5. The preparation method according to claim 3, characterized in that: The steps of preparing Ni SA / X-CTAB-MoS2 loaded with single-atom nickel are as follows: X-CTAB-MoS2 is mixed with a nickel source, and stirred to react under ultraviolet light to obtain a molybdenum disulfide-based composite material loaded with single-atom nickel; The mass ratio of X-CTAB-MoS2 to nickel source is (1:0.05)-(1:0.2); The nickel source is selected from one or more of Ni(NO3)2, nickel chloride, and nickel sulfate; The stirring reaction time is 4 to 8 hours.
6. The preparation method according to claim 3, characterized in that: The step of oxidizing X-CTAB-MoS2 to form a heterojunction X-CTAB-MoS2-MoO3 is as follows: mixing X-CTAB-MoS2 with an oxidant to react, and drying to obtain the X-CTAB-MoS2-MoO3; The oxidant is selected from one or more of H2O2, KMnO4, NaClO3 and NaClO4; The stirring and mixing reaction time is 12 to 24 hours.
7. The preparation method according to claim 3, characterized in that: The steps of loading single-atom nickel on X-CTAB-MoS2 and oxidizing it to form a heterojunction Ni SA / X-CTAB-MoS2-MoO3 are as follows: X-CTAB-MoS2 is stirred and mixed with an oxidant for reaction, and dried to obtain X-CTAB-MoS2-MoO3, and the X-CTAB-MoS2-MoO3 is mixed with a nickel source, and stirred and reacted under ultraviolet light to obtain the Ni SA / X-CTAB-MoS2-MoO3; The oxidant is selected from one or more of H2O2, KMnO4, NaClO3 and NaClO4; The stirring and mixing reaction is performed for 12 to 24 hours; The stirring reaction time is 4 to 8 hours.
8. The preparation method according to claim 3, characterized in that: The step of forming sulfur vacancies in situ by high-temperature heat treatment of X-CTAB-MoS2 to form X-CTAB-MoS2-SD is as follows: mixing and grinding the X-CTAB-MoS2 with a molten salt mixture, and calcining at a high temperature under an inert gas atmosphere to obtain the X-CTAB-MoS2-SD; The mass ratio of the X-CTAB-MoS2 to the molten salt mixture is (1:2)-(2:1); The temperature of high temperature calcination is 400-800°C, and the time of high temperature calcination is 2-6h; The inert gas of the inert atmosphere includes argon and / or nitrogen; The molten salt mixture is selected from two or more of KCl, LiCl and NaCl; In the X-CTAB-MoS2-SD, SD is sulfur-deficient molybdenum sulfide MoS z ; The sulfur-deficient molybdenum sulfide MoS z of 1 <Z<2。 9. Use of the defective carbon material-supported molybdenum disulfide-based composite material X-CTAB-Y according to claim 1 or 2 in electrocatalytic hydrogen evolution under acidic conditions.
10. Use of the defective carbon material-loaded molybdenum disulfide-based composite material X-CTAB-Y according to claim 1 or 2 in hydrogen production electrolyzers and fuel cells.
Citation Information
Patent Citations
Gasoline gas lamp refiner
CA150300A
Method for controlling morphology of MoS2 / RGO nanocomposite with surfactant
CN107140624A
Molybdenum disulfide / reductive graphene oxide / nickel nanoparticle composite material, as well as preparation method and application thereof
CN108607582A
Molybdenum disulfide-carbon nanotube photocatalytic composite material and synthesis method thereof
CN109589994A
Hydrothermal method for synthesizing molybdenum disulfide by taking elemental sulfur as sulfur source
CN115974158A